Next Generation Supply Chains: Trends and Opportunities - Wolfgang Kersten; Thorsten Blecker; Christian M. Ringle (epubli GmbH, 2014)
Today's demand patterns constantly claim for greener products from more sustainable supply chains. Handling these customer needs puts a constant pressure on the players: Ecological and social issues arise additionally to challenges like technology management and efficiency enhancement. Concurrently each of these holds incredible opportunities to separate from competitors, yet increases chain complexity and risks. This volume, edited by Wolfgang Kersten, Thorsten Blecker and Christian Ringle, provides valuable insights into: Sustainable Supply Chain Efforts, Handling Risks: Concepts towards robust SCM and Future Outlooks in Logistics.
urn:nbn:de:gbv:830-tubdok-12909; https://econpapers.repec.org/RePEc:zbw:hiclch:209198; https://econpapers.repec.org/RePEc:zbw:hiclch:209199; https://econpapers.repec.org/RePEc:zbw:hiclch:209200; https://econpapers.repec.org/RePEc:zbw:hiclch:209201; https://econpapers.repec.org/RePEc:zbw:hiclch:209202; https://econpapers.repec.org/RePEc:zbw:hiclch:209203; https://econpapers.repec.org/RePEc:zbw:hiclch:209204; https://econpapers.repec.org/RePEc:zbw:hiclch:209205; https://econpapers.repec.org/RePEc:zbw:hiclch:209206; https://econpapers.repec.org/RePEc:zbw:hiclch:209207; https://econpapers.repec.org/RePEc:zbw:hiclch:209208; https://econpapers.repec.org/RePEc:zbw:hiclch:209209; https://econpapers.repec.org/RePEc:zbw:hiclch:209210; https://econpapers.repec.org/RePEc:zbw:hiclch:209211; https://econpapers.repec.org/RePEc:zbw:hiclch:209212; https://econpapers.repec.org/RePEc:zbw:hiclch:209213; https://econpapers.repec.org/RePEc:zbw:hiclch:209214; https://econpapers.repec.org/RePEc:zbw:hiclch:209215; https://econpapers.repec.org/RePEc:zbw:hiclch:209216; https://econpapers.repec.org/RePEc:zbw:hiclch:209217; https://econpapers.repec.org/RePEc:zbw:hiclch:209218; https://econpapers.repec.org/RePEc:zbw:hiclch:209219; https://econpapers.repec.org/RePEc:zbw:hiclch:209220; https://econpapers.repec.org/RePEc:zbw:hiclch:209221; https://econpapers.repec.org/RePEc:zbw:hiclch:209222
Keywords: 650; Logistics; Supply Chain Management; Performance Management; Supply Chain Security; Logistik; Risikomanagement; Management; Nachhaltigkeit